Immunomodulatory effects of extracellular vesicles in glioblastoma - Low, Johannes Jun Wei; Sulaiman, Siti Aishah; Johdi, Nor Adzimah; Abu, Nadiah (Frontiers in Cell and Developmental Biology, 2022)
Glioblastoma (GB) being resistant to T cells immune response, aided by the immune privilege of the brain and presentation of an immunosuppressive tumor microenvironment, poses significant challenges in treatment. Extracellular vesicles (EVs) are cell-secreted nanosized vesicles that engage in intercellular communication via delivery of cargo, causing several downstream effects such as tumor progression and recipient cell modulation. Although the roles of EVs in cancer progression are well documented, their immunomodulatory effects are less defined. Herein, we focus on GB and discuss the immunomodulatory effects of EVs secreted by both tumor and immune cells in detail. The tumor to immune cells, immune cells to the tumor, and intra-immune cells EVs crosstalks are involved in various immunomodulatory effects. This includes the promotion of immunosuppressive phenotypes, apoptosis, and inactivation of immune cell subtypes, which affects the central nervous system and peripheral immune system response, aiding in its survival and progression in the brain.